2021
DOI: 10.31235/osf.io/aejgf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RGLS and RLS in Covariance Structure Analysis

Abstract: This paper assesses the performance of regularized generalized least squares (RGLS) and reweighted least squares (RLS) methodologies in a confirmatory factor analysis model. Normal theory maximum likelihood (ML) and GLS statistics are based on large sample statistical theory. However, violation of asymptotic sample size is ubiquitous in real applications of structural equation modeling (SEM), and ML and GLS goodness-of-fit tests in SEM often make incorrect decisions on the true model. The novel methods RGLS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, another new method, regularized GLS introduced by (Arruda and Bentler, 2017), is a good alternative to ML, GLS, and RLS. Recent study has shown that regularized GLS provides equivalent performance as RLS in both normal and non-normal data (Zheng and Bentler, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, another new method, regularized GLS introduced by (Arruda and Bentler, 2017), is a good alternative to ML, GLS, and RLS. Recent study has shown that regularized GLS provides equivalent performance as RLS in both normal and non-normal data (Zheng and Bentler, 2022).…”
Section: Discussionmentioning
confidence: 99%